2018
DOI: 10.1016/j.jconrel.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Tunable degradation of acetalated dextran microparticles enables controlled vaccine adjuvant and antigen delivery to modulate adaptive immune responses

Abstract: Subunit vaccines are often poorly immunogenic, and adjuvants and/or delivery vehicles, such as polymeric microparticles (MPs), can be used to enhance immune responses. MPs can also be used to understand cell activation kinetics and the significant impact antigen and adjuvant release has on adaptive immune responses. By controlling antigen and adjuvant release, we can determine if it is important to have precise temporal control over release of these elements to optimize the peak and duration of protective immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 83 publications
(105 reference statements)
3
65
2
Order By: Relevance
“…The in vivo study indicated that delivering PA and adjuvant in separate particles may provide a faster and stronger immune response toward anthrax. This finding supported the idea that adjuvant and antigen should be encapsulated in separate Ac-Dex particles optimized for each component with different CAC percentages (Chen et al, 2018b).…”
Section: Acetalated Dextransupporting
confidence: 79%
See 1 more Smart Citation
“…The in vivo study indicated that delivering PA and adjuvant in separate particles may provide a faster and stronger immune response toward anthrax. This finding supported the idea that adjuvant and antigen should be encapsulated in separate Ac-Dex particles optimized for each component with different CAC percentages (Chen et al, 2018b).…”
Section: Acetalated Dextransupporting
confidence: 79%
“…The difference might be attributed to the surface chemistry difference of the two materials due to the different degradation rate. A recent in vivo study (Chen et al, 2018b) showed that OVA loaded Ac-Dex particles with 20% cyclic acetal coverage (CAC) generated stronger antibody response during the entire experiment period compared to particles with 40 and 60% CAC. Notably, when the particles were used for adjuvant delivery, the immune activating behavior was different.…”
Section: Acetalated Dextranmentioning
confidence: 99%
“…This section will cover the electric field parameter and its impact on ES technology and on the generated MPs. The ES process only starts when a voltage is applied [10], depending on the formulations, the voltage can vary from 2.5 to 30 kV [15,31,41,57,58]. Correia et al investigated the effect of the electric field on designing PVDF MPs.…”
Section: Electric Fieldmentioning
confidence: 99%
“…This is influenced by the distance between the tip of the needle and the collector, and this distance influences the properties of the MPs, such as size and evaporation rate of the solvent [30,59]. Here, the distance between the tip of the needle and the collector can be adjusted from 6 to 30 cm [28,29,31,36,57,[60][61][62]. In this context, Faramarzi et al observed that when designing PLGA MPs at distances of 4, 7, 13, 19, and 26 cm, as the distance increases to values greater than 13 cm, the size of the MPs decreased slightly to a diameter of 3.6 µm [39].…”
Section: Collector Distancementioning
confidence: 99%
“…Measuring pH‐fluctuations noninvasively would certainly aid in the design of disease‐triggered drug release, and highly sensitive probes are being developed . Expanding the versatility of the particles and tailor them to the desired disease could include tuning the degree of acetalation and particle size to better suit the desired pH‐range, where the tuned release kinetics and stability could extend the prophylactic capacity of the particles …”
Section: Resultsmentioning
confidence: 99%